Evaluation of Zone Parking Policy Implementation in the Tunjungan Street Area, Surabaya City - Cristin Manalu; Alivia Nadhifa; Rahmi Rinanty; Shafa Dita (Universitas Negeri Gorontalo, 2026)
This article evaluates the implementation of the zone parking policy in the Tunjungan Street area of Surabaya City. The background of this research is driven by the severe traffic congestion caused by the high volume of vehicles parking on the roadside, despite existing regulations under Regional Regulation (Perda) Number 3 of 2018 concerning Parking Management. This study aims to determine the factual conditions in the field and comprehensively evaluate the policy using the six indicators of William N. Dunn's policy evaluation theory: effectiveness, efficiency, adequacy, equity, responsiveness, and appropriateness. The research method utilizes a descriptive qualitative approach. Primary data was collected through direct observation and in-depth face-to-face interviews using snowball sampling techniques, while secondary data was obtained through documentation of archives and regulations. The analysis relies on the Miles and Huberman interactive model, which includes data reduction, data display, and conclusion drawing. The validity of the data was tested using source, technique, and time triangulation. The results indicate that the policy has been highly effective, successfully reducing traffic congestion by approximately 80% by restoring the road to its full three-lane capacity. Efficiency is demonstrated by the Surabaya Transportation Agency's provision of adequate digital parking facilities, including applications, printers, and 1,500 smartphones for parking attendants. However, the evaluation identified several challenges: misuse of the digital payment system (QRIS) by rogue attendants, limited alternative parking capacity during peak weekend hours, and initial resistance from local MSMEs (UMKM) regarding access to their booths. In conclusion, the zone parking policy in Tunjungan Street is appropriate and responsive, but it requires stricter field supervision, the development of real-time digital parking slot tracking innovations, and the expansion of alternative parking capacities to fully optimize urban mobility.